VARIATIONS OF GLUCOSE 6-PHOSPHATE DEHYDROGENASE ACTIVITY IN VARIOUS TISSUES INDUCED BY METABOLIC ALKALOSIS, ACIDOSIS AND DIABETES (Journal of Sciences, Islamic Republic of Iran)
The effects of chronic metabolic acidosis, alkalosis and alloxan-induced ketoacidosis on G6PD activity of rat kidney, liver and erythrocytes were studied. Metabolic acidosis significantly increased the activity of kidney enzyme (55%) but decreased the liver (43%) and erythrocyte (38%) enzyme activities. Alkalosis did not make a significant change in the kidney or liver enzyme activity but slightly decreased that of the erythrocyte enzyme. In alloxan-induced diabetic rats, the rise in G6PD activity of kidney (69%) was associated with a decline in the enzyme activities of liver (50%) and erythrocytes (51%). It is suggested that in alloxan-induced diabetes, ketoacidosis is mainly responsible for the change in G6PD activity of various tissues and different organs do not respond similarly toward metabolic acidosis or alkalosis.